Perceptions of Inquiry-based Learning in Higher Education: A Case Study from North Macedonia - Brikena Xhaferi; Jeta Hamzai; Gezim Xhaferi (Journal of Linguistics and Language Teaching, 2024)
Inquiry-based learning (IBL) is a learner-centred approach based on using students' questions to facilitate learning. This approach is based on constructivist philosophy, particularly the work of Piaget, Dewey and Vygostky. Because it is suitable for developing students' critical thinking skills, modern educational methodologists call for its wider use in the classroom, not only in language teaching but also in other disciplines. The present study aims to explore teachers' and students' perceptions and classroom experiences of IBL in the EFL classroom at tertiary level. The research context is the South East European University (SEEU) in Tetovo, North Macedonia. The study, which uses two instruments, a survey and an interview for data collection, found that IBL has several benefits, including the development of communication skills, collaboration among students, critical thinking and active learning.